Copper chlorophyllin synthesis and its potential for application in the food industry - Cobo Boada, Sara Martina (2024)
The synthesis and characterization of copper chlorophyllin (Cu-Chl) presents great potential for industrial applications, especially as a natural food colorant. This study evaluated the extraction of chlorophyll from leaves and the synthesis of Cu-Chl, achieving a yield of 12.33% from spinach leaves. The solubility of Cu-Chl was enhanced through encapsulation, a crucial process for its efficient use in the food industry. The synthesis of Cu-Chl was confirmed by color changes, while the encapsulated Cu-Chl was characterized using UV-Vis and FT-IR spectroscopy. FT-IR analysis showed significant interactions between Cu-Chl and the encapsulation materials, confirming the effectiveness of the process. Encapsulation with maltodextrin and whey protein isolate significantly improved the solubility and stability of Cu-Chl, which are critical factors for its practical application. Attempts were made to isolate chlorophylls using column chromatography, providing information about the behavior of pigments in different polarity systems. Although complete isolation was not initially achieved, a subsequent method successfully isolated chlorophylls a and b, confirmed by TLC and UV-Vis. The encapsulated chlorophyll a showed improved solubility, and its FT-IR analysis revealed interactions with the encapsulation materials. This study suggests that the synthesis of Cu-Chl and the encapsulation of chlorophyll could transform agricultural waste rich in chlorophylls into high-value products, reducing the environmental impacts of practices such as open burning. Encapsulation is an effective strategy for improving the solubility of Cu-Chl and chlorophylls, paving the way for broader industrial applications. It is recommended to optimize extraction and synthesis processes and scale up production to maximize the industrial and environmental benefits of this technology.